The Influence of Price, Content, and Ease of Use on Consumer Attitude and Purchase Intention in the Video Streaming Industry - Malika EL Khaldi; Atik Aprianingsih (Universitas Prasetiya Mulya, 2026)
This study aimed to analyze the influence of price, content, and ease of use on consumer attitudes and purchase intentions toward local and global video streaming platforms in Indonesia, specifically comparing Vidio and Netflix. The research used a quantitative method and involved 107 respondents aged 17 and above who had experience using both platforms, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS‑SEM). The findings showed that price, content, and ease of use significantly affected consumer attitudes toward Vidio, while only price and ease of use had significant effects for Netflix. Content did not significantly influence attitudes for Netflix. Consumer attitude strongly influenced purchase intention for both platforms. This study filled a research gap by highlighting differences in attitude formation between local and global platforms and providing strategic insights for local providers to enhance competitiveness in Indonesia’s streaming industry.